IMPLEMENTASI PEMBELAJARAN SOSIAL EMOSIONAL DI ERA KURIKULUM MERDEKA DI SD BINAAN KECAMATAN PADANG UTARA - YUHELMI YUHELMI (LP2MTBM MAKARIOZ, 2022)
Social-emotional learning is essentially learning that is done collaboratively by the whole school community. This collaborative process enables children and adults in the school to acquire and apply knowledge, skills and positive attitudes regarding social and emotional aspects. This research aims to describe the guidance on the implementation of social emotional learning in the era of the independent curriculum in the assisted primary schools in Padang Utara sub-district. The type of research used in this study is the school action research method (PTS). The location of the research was at the assisted primary school in North Padang sub-district. The research was conducted in the July-December semester of the 2022/2023 academic year. The subjects of the principal action research were teachers at the assisted elementary schools in North Padang sub-district. The data collection technique of this school action research is through quantitative data obtained from observations and interviews. The data analysis technique used in this research is quantitative data analysis sourced from the acquisition of observation data. The results showed that based on the results of the research discussed in the previous section, it can be concluded that with the coaching to teachers regarding the implementation of social emotional learning, teachers become more understanding and able to control emotions and can apply social emotional learning to students in the learning system.